Allelochemical catechol comprehensively impedes bacterial blight of rice caused by Xanthomonas oryzae pv. oryzae. (December 2020) - Vishakha, Kumari; Das, Shatabdi; Banerjee, Satarupa; Mondal, Sandhimita; Ganguli, Arnab
Abstract: Xanthomonas oryzae pv. oryzae (Xoo) induces bacterial leaf blight (BLB), is known to be the most devastating disease of rice. The present investigation for the first time explains the antibacterial, anti-biofilm, and antivirulence potential of the simplest allelochemical catechol. Bacterial viability and growth are significantly reducing in catechol treatment. Further study also reveals that catechol also inhibits primary attachment and preformed biofilm of Xoo even at half MIC concentration. The half MIC concentration of catechol also induce a significant decrease in virulence factors like swimming, swarming, exopolysaccharide, and xanthomonadin production. Next, we investigate the possible antibacterial mode of action of catechol against Xoo. Results show that, the catechol caused oxidative stress and targets cell membrane for its antibacterial activity. Whereas, in silico study reveals that, catechol binds with the catalytic domain of XanA protein and this may be consider as a reason for antibiofilm activity of catechol. Moreover, in virulence assay on rice plants, we observe significant decrement in lesion length in catechol and Xoo co-treated rice leaves as compared with only Xoo treated leaves. All the results clearly show, allelochemical catechol to be a potential compound for the antibacterial, anti-biofilm, and antivirulence agent against Xoo and consequently mitigating the BLB disease advancement in rice. Graphical abstract: Image 1 Highlights: Allelochemical catechol inhibited the growth of Xanthomonas oryzae pv. oryzae (Xoo). Catechol showed anti-biofilm, antimotility, and antivirulence activity against Xoo. Catechol caused oxidative stress and subsequently targets cell membranes. Catechol binds with the catalytic domain of XanA protein as revealed by in silico study. Catechol reduced the lesion length caused by Xoo.